“Cometomancy” and Francisco Sánchez: an additional reflection on to causality - Rosero, Oriana; Jaimes, Fabian (Medicina Historica, 2023)
The search for a causal mechanism begins with the observation of an association, but there is a long way until the fact that is observed as an association can be configured as a cause. The scientific community has historically demanded tools that facilitate the determination of causality. In 1965, Sir Austin Bradford Hill proposed nine postulates, which were adapted by modern epidemiologists as criteria. Later, Alfredo Morabia in 1991 showed that the concern to establish causality came from more than two hundred years ago, recognizing a great similarity between Hill’s criteria and David Hume proposals for causality. However, the origin of these criteria could even come from four hundred years ago. In this reflection, we present the arguments taken from an ancient poem and contrast them with Hill’s criteria, to propose Francisco Sánchez as one of the first authors and physician trying to give a logical and rational order from association to causation, probably introducing the philosophical origin of the current Hill´s criteria.